ANALISIS PENGARUH SERVICE QUALITY, CUSTOMER TO CUSTOMER INTERACTION DAN SERVICE ATMOSPHERE TERHADAP SATISFACTION FIRM - VITA BRILIANA (Jurnal Bisnis dan Akuntansi, 2010)
The main purpose of this research is to identify the influence of service quality, service atmosphere and customer to customer interaction on satisfaction wth the firm. The method in this research is multiple regression. Data and information was collected by survey with questionnaire distribution to 100 respondents. Type of respondent in this research is consumer Natasha skin care of Wijaya representative on South Jakarta area. There are three conclusions. The first conclusion, there is a significant influence of service quality on satisfaction with the firm. The second conclusion, there is a significant influence of service atmosphere on satisfaction with the firm. The third conclusion, there is a significant influence of customer to customer interaction on satisfaction with the firm.